2021
DOI: 10.1051/0004-6361/202141744
|View full text |Cite
|
Sign up to set email alerts
|

Dark Energy Survey Year 3 Results: Galaxy mock catalogs for BAO analysis

Abstract: The calibration and validation of scientific analysis in simulations is a fundamental tool to ensure unbiased and robust results in observational cosmology. In particular, mock galaxy catalogs are a crucial resource to achieve these goals in the measurement of baryon acoustic oscillation (BAO) in the clustering of galaxies. Here we present a set of 1952 galaxy mock catalogs designed to mimic the Dark Energy Survey Year 3 BAO sample over its full photometric redshift range 0.6 < zphoto < 1.1. The mocks ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…We create a set of 1952 mock catalogs of the DES Y3 BAO sample that reproduce with high accuracy the principal properties of the data: (i) the sample observational volume, (ii) the abundance of galaxies, true redshift distribution and photometric redshift uncertainty, and (iii) the clustering as a function of redshift. We refer the reader to [40] for further details, and highlight here only the basic features of the ICE-COLA mocks used for this work.…”
Section: A Ice-cola (Quasi-n-body) Mocksmentioning
confidence: 99%
See 4 more Smart Citations
“…We create a set of 1952 mock catalogs of the DES Y3 BAO sample that reproduce with high accuracy the principal properties of the data: (i) the sample observational volume, (ii) the abundance of galaxies, true redshift distribution and photometric redshift uncertainty, and (iii) the clustering as a function of redshift. We refer the reader to [40] for further details, and highlight here only the basic features of the ICE-COLA mocks used for this work.…”
Section: A Ice-cola (Quasi-n-body) Mocksmentioning
confidence: 99%
“…The replications mentioned above introduce strong correlations among the measured wðθÞ of tomographic bins that are not adjacent. This is discussed more in detail in [40] where it is shown that up to a ∼10% of the particles are repeated (depending on the tomographic bin combination) once we impose the DES Y3 footprint and nðzÞ. This leads to nonzero covariances for tomographic bins that have no redshift overlap otherwise.…”
Section: A Ice-cola (Quasi-n-body) Mocksmentioning
confidence: 99%
See 3 more Smart Citations